The Effectiveness of Online Learning for Low Grades in Elementary Schools: Efektifitas Pembelajaran Daring Untuk Kelas Rendah di Sekolah Dasar - Ari Susandi; Khosiah , Nur; Soliha, Imro Atus (Universitas Muhammadiyah Sidoarjo, 2021)
The purpose of this study is to describe the effectiveness of learning during low-grade classes at Muhammadiyah elementary school in the city of Probolinggo which still has some depth in applying it using qualitative descriptive research methods then for the data technique using a questionnaire or online questionnaire using the google form feature which is shared. to 133 respondents from guardians of grade one to grade three with data sources obtained from principals, educators, parents, students, learning with an online system (brave) is still effectively carried out by implementing several strategies, we can see that it has not been effectively done By implementing several strategies, we can see that the results of the questionnaire that have been distributed to all respondents through online media in the form of google form have not been effective, there are still many who respond disagree with the five questions that have been made and asked to students and it seems that it is not yet effective.